Exome sequencing in patient‐parent trios suggests new candidate genes for early‐onset primary sclerosing cholangitis. (11th March 2021) - Haisma, Sjoukje‐Marije; Weersma, Rinse K.; Joosse, Maria E.; de Koning, Barbara A. E.; de Meij, Tim; Koot, Bart G. P.; Wolters, Victorien; Norbruis, Obbe; Daly, Mark J.; Stevens, Christine; Xavier, Ramnik J.; Koskela, Jukka; et al.
Abstract: BACKGROUND & AIMS: Primary sclerosing cholangitis (PSC) is a rare bile duct disease strongly associated with inflammatory bowel disease (IBD). Whole‐exome sequencing (WES) has contributed to understanding the molecular basis of very early‐onset IBD, but rare protein‐altering genetic variants have not been identified for early‐onset PSC. We performed WES in patients diagnosed with PSC ≤ 12 years to investigate the contribution of rare genetic variants to early‐onset PSC. METHODS: In this multicentre study, WES was performed on 87 DNA samples from 29 patient‐parent trios with early‐onset PSC. We selected rare (minor allele frequency < 2%) coding and splice‐site variants that matched recessive (homozygous and compound heterozygous variants) and dominant (de novo) inheritance in the index patients. Variant pathogenicity was predicted by an in‐house developed algorithm (GAVIN), and PSC‐relevant variants were selected using gene expression data and gene function. RESULTS: In 22 of 29 trios we identified at least 1 possibly pathogenic variant. We prioritized 36 genes, harbouring a total of 54 variants with predicted pathogenic effects. In 18 genes, we identified 36 compound heterozygous variants, whereas in the other 18 genes we identified 18 de novo variants. Twelve of 36 candidate risk genes are known to play a role in transmembrane transport, adaptive and innate immunity, and epithelial barrier function. CONCLUSIONS: The 36 candidate genes for early‐onset PSC need further verification in other patient cohorts and evaluation of gene function before a causal role can be attributed to its variants.